Description of a new species of deepwater catshark Apristurus yangi n.sp (Carcharhiniformes: Pentanchidae) from Papua New Guinea - White, William T.; Mana, Ralph R.; Naylor, Gavin J.p. (Zootaxa, 2017)
Apristurus yangi, a new species of deepwater catshark, is described from Papua New Guinea based on two specimens collected during recent deepwater surveys. The new species belongs to the longicephalus-group which is characterised by its very long snout compared to members of the brunneus-group and spongiceps-groups. Apristurus yangi differs from its closest congeners in a combination of the following characters: 8 intestinal spiral valves; mouth width 7.9–8.6% TL; 32–33 monospondylous centra; 38 precaudal-diplospondylous vertebrae; small in size (female holotype mature at 437 mm TL); egg case small ( 5.9 cm long) and with faint longitudinal striations.